Clinical definitions of melioidosis. - Cheng, A; Currie, B; Dance, D; Funnell, S; Limmathurotsakul, D; Simpson, A; Peacock, S (American Society of Tropical Medicine and Hygiene, 2013)
Clinical definitions of melioidosis and inhalation-acquired melioidosis (Burkholderia pseudomallei infection) are described together with the evidence used to develop these definitions. Such definitions support accurate public health reporting, preparedness planning for deliberate B. pseudomallei release, design of experimental models, and categorization of naturally acquired melioidosis.